Tanshinone IIA combined with cisplatin synergistically inhibits non‐small‐cell lung cancer in vitro and in vivo via down‐regulating the phosphatidylinositol 3‐kinase/Akt signalling pathway - Liao, Xiao‐Zhong (Phytother Res, 2019)
Cisplatin represents one of the first‐line drugs used for non‐small‐cell lung cancer treatment. However, considerable side effects and the emergence of drug resistance are becoming critical limitations to its application. Combinatorial strategies may be able to extend the use of cisplatin. Both Tanshinone IIA and cisplatin inhibit non‐small‐cell lung cancer cell growth in a time‐ and dose‐dependent manner. When Tanshinone IIA was combined with cisplatin at a ratio of 20:1, they were observed to exert a synergistic inhibitory effect on non‐small‐cell lung cancer cells. The combination treatment was shown to impair cell migration and invasion, arrest the cell cycle in the S phases, and induce apoptosis in A549 and PC9 cells in a synergistic manner. KEGG pathway analysis and molecular docking indicated that Tanshinone IIA might mainly influence the phosphatidylinositol 3‐kinase‐Akt signalling pathway. In all treated groups, the expression levels of Bax and cleaved Caspase‐3 were up‐regulated, whereas the expression levels of Bcl‐2, Caspase‐3, p‐Akt, and p‐PI3K proteins were down‐regulated. Among these, the combination of Tan IIA and cisplatin exhibited the most significant difference. Tanshinone IIA may function as a novel option for combination therapy for non‐small‐cell lung cancer treatment.